«GREEN» LOGISTICS AS A TOOL TO ENSURE ENVIRONMENTAL SECURITY AND INSTITUTIONAL INNOVATION SUBSOIL EUROPEAN ARCTIC - M. N. Dudin; N. I. Komkov; N. V. Lyasnikov (Модернизация, инновация, развитие)
This article is an overview of the major logistics and technology solutions to be implemented to streamline the subsoil use in the European Arctic. The theme of this work is very urgent, because Russia, despite the high resource base is underdeveloped institutional framework and resource extraction is characterized by the maximum level of loss of potential gross value of the hydrocarbon potential.The purpose of this article is to study Russian priorities at national and regional level, related to mining, through the use of «green» logistics as an instrument for environmental safety and institutional innovation subsoil of the European Arctic.Methodology. The methodological basis of this article are comparative, economic and statistical analysis methods.The results of this paper have become the solutions to problems, to achieve this goal, in particular: a substantiated conclusion that the Arctic is a world heritage and «climate laboratory» of the planet, so the development of the resource, industrial, transport and logistics potential of the region need to be based on «green» technologies; The article describes four environmentally-oriented direction (creating material and technical base, the formation of a safe icebreaker fleet, the development of new navigation and communication systems, power supply), which will enable to master the industrial, transport and logistics potential of the Arctic with minimal anthropogenic load.Conclusions. The following basic conclusions were as follows: first, subarctic and arctic areas are world heritage, so the development of deposits on them should be in the interest of the world community on a non-discriminatory  basis; secondly, hydrocarbon reserves, concentrated in the European Arctic, currently can not be extracted without environmental impacts, access to these resources is limited due to lack of development of the transport component, therefore, should be used aggressive techniques of extraction of primary energy resources of the Arctic fields.